The Effect of Urban Welfare on Resident Labor Supply in China: Mediating Effects of Social Interaction and Cynicism - Lulin Zhou; Renjie Nie; Zhiyuan Chen; Xinglong Xu (SAGE Open)
China’s labor market, being the largest globally, is facing challenges due to factors such as population aging and polarization of population movements, this study aims to examine the relationship between urban welfare and labor supply among urban residents in China, considering the mediating roles of social interaction and cynicism. OLS regression analysis using STATA16 software was conducted to test the correlations between urban welfare, social interaction, cynicism, and labor supply. The mediation effects were examined through KHB regression, demonstrating the specific roles of social interaction and cynicism as mediators. This study concludes that urban welfare has a significant negative impact on the labor supply of urban residents in China. Social interaction plays a positive mediating role, emphasizing its importance in the relationship between urban welfare and labor supply. Cynicism also plays a negative mediating role, albeit with a minor effect. When both social interaction and cynicism are considered, their joint effect is negative, with social interaction exerting a stronger mediation effect. Furthermore, the study highlights the gender and regional differences in the impact of urban welfare, social interaction, and cynicism on labor supply. These findings provide valuable insights for policymakers to enhance urban welfare programs and promote labor supply in China.